Effects of Rusanda Spa Balneotherapy Combined with Calcipotriol on Plaque Psoriasis - Golušin, Zoran; Jovanović, Marina; Magda, Nataša; Stojanović, Slobodan; Matić, Milan; Petrović, Aleksandra (Vojnosanitetski pregled, 2015)
Introduction: Treatment of psoriasis is very complex and universally or uniquely effective treatment modalities are still being explored. Apart from conventional treatment, which includes topical calcipotriol (vitamin D3 analogue), balneotherapy is receiving increased attention worldwide. Being part of climatotherapy, balneotherapy is defined as the use of natural environmental factors in the treatment of health conditions, whereas in the treatment of psoriasis it means use of mineral baths and peloids.Aim: The aim of this study was to examine therapeutic efficacy of mineral waters and peloids of the Rusanda Spa on plaque psoriasis in patients also treated with calcipotriol.Methods: The study included 60 patients divided into two groups. The first group included patients treated with mineral waters, peloids and calcipotriol in the Rusanda Spa, while the second group included outpatients treated only with calcipotriol. The study lasted 21 days, and each patient was followed up for at least one month after ending the treatment. The treatment efficacy was measured by PASI scores on days 0, 7, 14, 21 and on 30th day after the end of therapy.Results: After thee weeks of treatment in the Rusanda Spa, the first group showed a decrease in PASI score by 59.45%, whereas in the group of outpatients treated by calcipotriol it was 39.34%. On the 30th day following treatment, the first group presented with a PASI score reduction of 58.44%, and the second group of 34.78%. The therapeutic efficacy of mineral waters and peloids combined with calcipotriol showed to be significantly higher in regard to monotherapy with calcipotriol (p